Entrepreneurship Study and Its Impact on Students’ Intention to Start Up: A Sample Case Study of Students Belonging to Two Universities of Tunisia - Zouari, Soufien; Mabrouki, Kais (Rescollacom (Research Collaborations Community), 2024)
The present paper examines the impact of entrepreneurship education on students’ intention to start up business. Using a sample of young Tunisian students from both Sfax and Sousse (these are two tows in Tunisia) universities, we propose to determine the significant factors influencing their entrepreneurial intention. Our econometric results have revealed that the composite variables , i.e, the student’s internal and external socio-cultural background, the students’ profile in terms of their theoretical and practical knowledge in new business start-up and the students’ characteristics (age and, above all, educational level), are the most determining variables affecting students’ intention to engage in business start-ups. The gender variable has no significant effect on entrepreneurial behavior.